2019
DOI: 10.1021/acs.iecr.9b03346
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Investigation of Low-Temperature Oxidation Characteristics and Mechanisms of Heavy Crude Oil

Abstract: During an in situ combustion (ISC) process, low-temperature oxidation (LTO) is of vital significance for the follow-up oxidation reactions and oil recovery. Herein, this work is intended to carry out in-depth investigations regarding LTO of heavy crude oil. Alterations of evolved gas compositions and oil properties caused by LTO were first examined. Then the particular focus was placed on the analyses of electron paramagnetic resonance (EPR) and nuclear magnetic resonance (NMR) of oxidized oil samples. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This should not be construed as absence of conversion at ambient temperature or indefinite stability of the asphaltenes in solution. There is ample evidence to indicate that oxidation of heavy oil and asphaltenes will proceed at ambient temperature over time (oxidative weathering), and this process can be accelerated by increasing the partial pressure without resorting to an increase in temperature …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This should not be construed as absence of conversion at ambient temperature or indefinite stability of the asphaltenes in solution. There is ample evidence to indicate that oxidation of heavy oil and asphaltenes will proceed at ambient temperature over time (oxidative weathering), and this process can be accelerated by increasing the partial pressure without resorting to an increase in temperature …”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence to indicate that oxidation of heavy oil and asphaltenes will proceed at ambient temperature over time (oxidative weathering), and this process can be accelerated by increasing the partial pressure without resorting to an increase in temperature. 22 3.2. Reaction of Asphaltenes and 1,2-Dihydronaphthalene.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…To further understand the LTO reaction pathways of heavy oil, Zhao et al investigated alterations of gaseous product compositions and oxidized oil properties caused by LTO. The results indicate that LTO reactions were carried out at lower levels as the oxidation temperatures lowered, which was demonstrated by a lower H/C and higher content of high molecules with polycyclic aromatic hydrocarbons [25]. Zhao et al characterized the compositional changes of the heavy oil due to LTO through gas chromatograph-mass spectroscopy and negative ion electrospray Fourier transform-ion cyclotron resonance mass spectrometry; the results showed that the condensation of aromatics, as well as aromatization and condensation of other compounds, were intensified below 200 • C, and that chain saturated aliphatic, monocyclic, bicyclic, and tricyclic naphthenic acids were the main acidic components in the oxidized oils [26].…”
Section: Introductionmentioning
confidence: 91%
“…; then, static isothermal oxidation experiments were carried out for 3 days in a muffle furnace at specific temperatures (50, 100, 150, 200, 250, 300, and 350 • C) and a constant pressure of 2.98 MPa (the original pressure of the FC oilfields). After isothermal oxidation reactions of FC extra-heavy oil at various experiment temperatures, oxidized oils and gaseous products were collected [25,27].…”
Section: Static Isothermal Oxidation Experiments and Physical Propert...mentioning
confidence: 99%
“…With the decrease of the crude oil temperature during pipelining, the wax becomes less soluble and crystallizes out of the crude oil. The precipitated wax crystals accompanying the aggregated asphaltene particles change the crude oils from simple Newtonian fluids to complex non-Newtonian fluids, and even induce gelation [2]. Therefore, crude oils containing high asphaltene and wax contents often have a high pour point and high viscosity, which is adverse for the safety and economic operation of crude oil transportation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%